Environmental protection of the North Sea - Newman, P. J.; Agg, A. R. (Heinemann Professional Publishing, 1988)
Environmental Protection of the North Sea focuses on measures and initiatives for the protection of the North Sea. The book first discusses the physical features, North Sea resources, and biological considerations. The compilation then takes a look at the distribution of anthropogenic organic compounds in the North Sea, including analytical aspects and reporting format for polychlorinated biphenyls (PCBs); transport of PCB in abiotic phases in rivers, estuaries, and the North Sea; and PCB in biota. The text examines the environmental impacts of organic chemicals. History of pollution; environm.